How GIS could be used as a tool to enhance the tourism sectors? A case study of Eritrea - Afsar Alam, Mohammad (Journal for Geography, 2012)
The tourism phenomena have attracted not only Eritrea, but almost the entire world. Tourism is being recognized as a source of economic benefits to a country by a way of gaining foreign exchange and employment generation on a truly international scale. It also makes a tremendous contribution to the improvement of social and political understanding. Though, Eritrea’s tourism industry is currently rated as one of the lowest foreign exchange earners in the country, the potential of tourism industry to become a leading source of foreign exchange earnings in Eritrea has not been far realized. It is evident that the country’s tourism potential has not been fully explored and marketed. Though several attempts have been made to enhance its rapid development, but these efforts have suffered some major drawbacks due to lack of a comprehensive spatial database of tourism facilities and destinations. By using GIS, a common platform can be defined to provide a spatial databank with integrated multimedia features. This paper discusses the use of GIS as a tool for archiving, analyzing, and displaying of tourism information to enhance the tourism sectors in Eritrea.
Keywords: GIS; tourism; Eritrea